Integrating engineering design and analysis using a parameter constraint graph approach. (July 2015) - He, Bin; Hou, Shuangchao; Song, Wei
With the present gap between engineering design and analysis, designers are often hindered in their efforts to explore design alternatives and ensure product robustness. This paper is devoted to parameter constraint graph approach-based dynamic information association and integration between the design model and analysis model. After the description of the gap between design and analysis is analyzed, the modeling and representation method of the product parameter constraints model are proposed. With the help of a product virtual prototyping element model, it can be simplified to a product parameter constraint graph to support an integrated model for multidisciplinary virtual prototyping of complex products. An integrated design and analysis method based on the parameter constraint graph approach is proposed based on the parameterized design method for analysis. The decoupling method of parameter constraints for multidisciplinary virtual prototyping is also discussed in detail in five steps. The integrated design and analysis of an automatic pipe racking robot in an offshore platform are given as an example, which demonstrates that the methodology is obviously helpful in improving the associability of design–analysis models.